Silver Nanowire‐Based Catalysts for Oxygen Reduction Reaction in Alkaline Solution. Issue 20 (18th August 2021) - Linge, Jonas Mart; Kozhemyakin, Daniil; Erikson, Heiki; Vlassov, Sergei; Kongi, Nadezda; Tammeveski, Kaido
Abstract: The electrocatalytic activity of commercial silver nanowires (AgNWs) with different diameters (35, 90, and 120 nm) was investigated towards the oxygen reduction reaction (ORR) in 0.1 M KOH solution. The rotating disc electrode (RDE) data analysis revealed that the ORR onset potential and half‐wave potential shift positively for AgNWs as compared to a polycrystalline Ag electrode. The enhanced ORR performance of AgNWs with a diameter of 35 nm was attributed to the elongated porous structure of the catalyst material, which facilitated the mass transport in the catalyst layer. The Koutecky‐Levich analysis was used to determine the kinetic parameters of O2 reduction and to confirm that the ORR proceeds via 4‐electron pathway on AgNW‐modified electrodes. Stability tests showed that 35 nm thick AgNWs had high stability during long‐term potential cycling. Based on the obtained results, the AgNWs have great potential as efficient catalysts for alkaline membrane fuel cell technologies. Abstract : In this work the ORR was tested on 35, 90 and 120 nm diameter AgNWs. The enhanced ORR performance of AgNWs is attributed to the elongated porous structure of the catalyst material. AgNWs show great potential for application in alkaline membrane fuel cells and other electrochemical energy technology devices.